Enhancing Communication Performance: Addressing Propagation Effects and Noise Sources - Goshu, Belay Sitotaw (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
This study investigates signal attenuation and chromatic dispersion, employing mitigation strategies to enhance signal quality in optical fibers. The results demonstrate that the original signal exhibits uniform propagation, but interference from noise leads to increased signal degradation, as indicated by the signal-to-noise ratio (SNR) statistics. The mean SNR of the original signal was 3.4147 dB, which increased to 5.0549 dB under noisy conditions. The SNR sharply dropped to -5.2713 dB after applying quantum squeezing techniques, indicating a discernible loss and a noise reduction. The SNR was raised to -4.8290 dB after noise filtration, suggesting a high performance but still below the initial signal quality. The effectiveness of the techniques was demonstrated through statistical analysis, including a t-test, which revealed variations in SNR under different conditions. Additionally, SNR variation with distance was explored, showing an increase proportional to the square of the distance, underscoring the need for distance considerations in optical communication design. Overall, this research provides insights into the complex interplay between signal enhancement methods and their impact on optical fiber communications.